Analisis Faktor Yang Berhubungan Dengan Kepatuhan Protokol Kesehatan Pada Masa Pandemi Covid 19 Di Kelurahan Rawalumbu Kota Bekasi - Yesica Damayanti Manalu; Milla Evelianti Saputri; Tommy J.F Wowor (Malahayati Nursing Journal, 2022)
ABSTRACT Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). SARS-CoV-2 is a new type of coronavirus that has never been previously identified in humans. Common signs and symptoms of COVID-19 infection are symptoms of acute respiratory distress such as fever, cough, and shortness of breath. The average incubation period for COVID-19 is 5-6 days with the longest incubation period being 14 days. In severe cases of COVID-19, it can cause pneumonia, acute respiratory syndrome, kidney failure, and even death. It is known that there is a relationship between knowledge, attitude, motivation, and infrastructure with health protocol compliance in RW 37 Bekasi City. The type of research used is a quantitative method, this research is descriptive-analytic by using a cross-sectional approach. This sampling was taken using a measuring instrument using a questionnaire and a questionnaire measuring instrument and the data obtained would be analyzed univariately and bivariate using the chi-square test. The results of this study indicate that there is a significant relationship between knowledge and health protocol compliance with p-value (0.048) 0.05, attitude with health protocol compliance with p-value (0.013) 0.05, motivation with health protocol compliance with p-value (0.000) 0.05 and infrastructure with health protocol compliance with p-value (0.013) 0.05. There is a significant relationship between knowledge, attitudes, motivation, and infrastructure with health protocol compliance. Keywords: Compliance COVID-19, Knowledge, Attitude, Motivation, Infrastructure ABSTRAK Coronavirus Disease 2019 (COVID-19) adalah penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2). SARS-CoV-2 merupakan coronavirus jenis baru yang belum pernah di identifikasi sebelumnya pada manusia. Tanda dan gejala umum infeksi COVID-19 yaitu gejala gangguan pernapasan akut seperti demam, batuk dan sesak napas. Masa inkubasi covid-19 rata-rata 5-6 hari dengan masa inkubasi terpanjang 14 hari. Pada kasus COVID-19 yang berat dapat menyebabkan pneumonia, sindrom pernapasan akut, gagal ginjal, dan bahkan kematian. Tujuan diketahui hubungan pengetahuan, sikap, motivasi dan sarana prasarana dengan kepatuhan protokol kesehatan di RW 37 Kota Bekasi. Jenis penelitian yang digunakan adalah metode kuantitatif, penelitian ini bersifat deksriptif analitik dengan menggunakan pendekatan cross sectional. Pengambilan sampel ini dengan alat ukur menggunakan angket dan alat ukur kuesioner dan data yang diperoleh akan di analisis secara univariat dan bivariat menggunakan uji chi square. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang signifikan antara pengetahuan dengan kepatuhan protokol kesehatan dengan p value (0,048) 0,05, sikap dengan kepatuhan protokol kesehatan dengan p value (0,013) 0,05, motivasi dengan kepatuhan protokol kesehatan dengan p value (0,000) 0,05 dan sarana prasarana dengan kepatuhan protokol kesehatan dengan p value (0,013) 0,05. Terdapat hubungan yang signifikan antara pengetahuan, sikap, motivasi dan sarana prasarana dengan kepatuhan protokol kesehatan. Kata Kunci: Kepatuhan Covid-19, Pengetahuan, Sikap, Motivasi, Sarana Prasarana